Courageous conversations about race a field guide for achieving equity in schools - Singleton, Glenn E. (Glenn Eric) (Thousand Oaks, California Corwin, a Sage Company, 2015)
Create a systemwide plan for transforming the district office, schools, and classrooms into places that truly support ALL students achieving their highest levels! This updated edition of the bestseller continues to explain the need for candid, courageous conversations about race so that educators may understand why achievement inequality persists and learn how they can develop a curriculum that promotes true educational equity and excellence. NEW! Revised Courageous Conversation Compass NEW! Racial autobiographies NEW! Case study on St. Paul Public Schools, which has stayed on track with the Courageous Conversation protocol and framework NEW! Links to video segments of the author describing the work REVISED! Activities and checklists for school and district leaders REVISED! Action and implementation steps.
Breaking the silence : ushering in courageous conversation about race -- pt. I. Passion : an essential characteristic of racial equity leadership -- What's so courageous about this conversation? -- Why race? -- Agreeing to talk about race -- pt. II. Practice : the foundation of racial equity leadership -- The first condition : getting personal right here and right now -- The second condition : keeping the spotlight on race -- The third condition : engaging multiple racial perspectives -- The fourth condition : keeping us all at the table -- The fifth condition : what do you mean by "race"? -- The sixth condition : let's talk about whiteness -- pt. III. Persistence : the key to racial equity leadership -- How racial equity leaders eliminate systemic racial disparities -- Exploring a systemic framework for achieving equity in schools -- Courageous conversation as a strategy for achieving equity in schools.
Includes bibliographical references (pages 277-280) and index.
Keywords: Educational equalization -- United States; Academic achievement -- United States; United States -- Race relations